2016
DOI: 10.1038/ncomms13289
|View full text |Cite
|
Sign up to set email alerts
|

Pupil fluctuations track rapid changes in adrenergic and cholinergic activity in cortex

Abstract: Rapid variations in cortical state during wakefulness have a strong influence on neural and behavioural responses and are tightly coupled to changes in pupil size across species. However, the physiological processes linking cortical state and pupil variations are largely unknown. Here we demonstrate that these rapid variations, during both quiet waking and locomotion, are highly correlated with fluctuations in the activity of corticopetal noradrenergic and cholinergic projections. Rapid dilations of the pupil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

107
938
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 749 publications
(1,121 citation statements)
references
References 61 publications
107
938
10
Order By: Relevance
“…In agreement with studies in primates and rodents (Aston-Jones and Cohen, 2005; Joshi et al, 2016; Reimer et al, 2016), we found that noradrenergic locus coeruleus neurons were significantly correlated with alertness states, displaying greater activity prior to fast RT trials (Figures 3B and 3C). We also found several other neuromodulatory cell types correlated with high alertness states: cocaine- and amphetamine-regulated transcript (CART) neurons in the tegmentum (Figure 3B); cholinergic neurons in the tegmentum; and dopaminergic, serotonergic, and neuropeptide-Y-expressing cells in the hypothalamus (Figures 3C and S3).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In agreement with studies in primates and rodents (Aston-Jones and Cohen, 2005; Joshi et al, 2016; Reimer et al, 2016), we found that noradrenergic locus coeruleus neurons were significantly correlated with alertness states, displaying greater activity prior to fast RT trials (Figures 3B and 3C). We also found several other neuromodulatory cell types correlated with high alertness states: cocaine- and amphetamine-regulated transcript (CART) neurons in the tegmentum (Figure 3B); cholinergic neurons in the tegmentum; and dopaminergic, serotonergic, and neuropeptide-Y-expressing cells in the hypothalamus (Figures 3C and S3).…”
Section: Resultssupporting
confidence: 91%
“…Here, we used cell-type-specific neural activity recording—spanning phylogenetically distant vertebrate species—to show that variability in the internal state of alertness during behavior is encoded by a specific set of multiple distinct neuromodulatory cell types. These findings extend previous work establishing that alertness states are encoded by noradrenergic neurons in the locus coeruleus (Aston-Jones and Cohen, 2005; Joshi et al, 2016; Reimer et al, 2016). While the possibility of alternative neuromodulatory systems for control of alertness has been postulated (Marrocco et al, 1994; Robbins, 1997), here we specifically document the many relevant cell types in two vertebrate species and reveal that the set of neuromodulatory circuits encoding alertness is an ancient and fundamental feature of the vertebrate brain.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus people with high tonic LC activity should have a lower pupil change overall and, conversely, people with low tonic LC should have higher pupil change overall. In contrast, at the trial-by-trial level, work in monkeys and in mice has suggested that moment-to-moment pupil diameter changes track phasic LC firing (Joshi et al, 2016;Reimer et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from a number of authors suggests that pupil-linked arousal processes, putatively driven by the locus coerulues norepinephrine system (Aston-Jones & Cohen, 2005;Eldar, Cohen, & Niv, 2013;Joshi, Li, Kalwani, & Gold, 2016;Rajkowski, 1993;Reimer et al, 2016), are well placed to modulate these four di erent sources of suboptimality. First, with regard to noise, changes in pupil response have been shown as indicators of various cognitive states and processes such as e ort, arousal, mood, attention and memory (Aston-Jones & Cohen, 2005;Sara, 2009).…”
Section: Introductionmentioning
confidence: 99%